A scoping review of practice recommendations for clinicians' communication of uncertainty - Niki M. Medendorp; Anne M. Stiggelbout; Cora M. Aalfs; Paul K. J. Han; Ellen M. A. Smets; Marij A. Hillen (Wiley, 2021)
Abstract Background Health‐care providers increasingly have to discuss uncertainty with patients. Awareness of uncertainty can affect patients variably, depending on how it is communicated. To date, no overview existed for health‐care professionals on how to discuss uncertainty. Objective To generate an overview of available recommendations on how to communicate uncertainty with patients during clinical encounters. Search strategy A scoping review was conducted. Four databases were searched following the PRISMA‐ScR statement. Independent screening by two researchers was performed of titles and abstracts, and subsequently full texts. Inclusion criteria Any (non‐)empirical papers were included describing recommendations for any health‐care provider on how to orally communicate uncertainty to patients. Data extraction Data on provided recommendations and their characteristics (eg, target group and strength of evidence base) were extracted. Recommendations were narratively synthesized into a comprehensible overview for clinical practice. Results Forty‐seven publications were included. Recommendations were based on empirical findings in 23 publications. After narrative synthesis, 13 recommendations emerged pertaining to three overarching goals: (a) preparing for the discussion of uncertainty, (b) informing patients about uncertainty and (c) helping patients deal with uncertainty. Discussion and conclusions A variety of recommendations on how to orally communicate uncertainty are available, but most lack an evidence base. More substantial research is needed to assess the effects of the suggested communicative approaches. Until then, health‐care providers may use our overview of communication strategies as a toolbox to optimize communication about uncertainty with patients. Patient or public contribution Results were presented to stakeholders (physicians) to check and improve their practical applicability.